An analysis on children of prostitute’s confidence and efforts to deal with the problem (a case study at kompleks butung) - Rukaya . (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
The aim of this research was to investigate: (i) the confidence of children of prostitute (COP) at Kompleks Butung such as: prefer being alone, full of doubt, uncompetitive, unsupportive, very sensitive, attention seeker, and afraid of making mistakes. (ii) The causing factors of the COP’s lack of confidence at Kompleks Butung are; (a) Internal Factors such as self-concept, physical condition, and life experience. (b) External Factors such as education, and environment. (iii) The impacts of confidence problem of the COP on ID and IR; (a) Academic Impact such as low grades, (b) Social Impact such as self-withdraw, (c) Personal Impact such as hatred to parents, anxiety, loneliness, depression, and even intention to commit suicide, and (iv) School counselors have done some efforts to solve the problems through: project work, environment acknowledgment, and classical guideline services.